Parkinson's disease constipation effect of electroacupuncture at ST25 through colonic motility and enteric neuropathology - Song, Li-zhe-xiong; Li, Yuan; Qian, Xu; Xu, Na; Yu, Zhi; Dai, Jing-wen; Xu, Bin; Hu, Xuan-ming (Frontiers in Neurology, 2023)
Background The enteric nervous system (ENS) plays a central role in developing Parkinson's disease (PD) constipation, and the regulation of the ENS may be a key component in treating PD constipation. Electroacupuncture (EA) can effectively treat constipation symptoms in PD, but research on its specific mechanisms, especially in terms of ENS, is relatively lacking. Therefore, we investigated whether EA at ST25 promotes the restoration of ENS structure and colonic motor function in the rotenone-induced PD constipation rat model. Methods In this study, we evaluated constipation symptoms by stool characteristics, excretion and water volume, and whole gut transit time and observed colonic motility regulation through colonic motion detection and pathological changes in the colonic myenteric nervous plexus by transmission electron microscopy and immunofluorescence staining. Results EA significantly improved the constipation symptoms and positively adjusted the colonic motility in rotenone-induced PD constipation rats. At the same time, EA reversed the rotenone-induced colonic myenteric nervous plexus injury and regulated the ratio of inhibitory and excitatory neurotransmitters. Conclusion Our results indicate that EA treatment of PD constipation may be mediated through the adjustment of ENS.